Comparison of Different Time Delay Compensation Methods for Networked DC Motor Speed Control - Suulker, Cem; Emirler, Mumin Tolga (IEEE, 2019)
In this paper, different time delay compensation methods are applied to networked DC motor speed control such as Smith predictor, communication disturbance observer (CDOB), double disturbance observer (DDOB). The PI speed control system structures augmented with these methods are introduced. The reference tracking and external disturbance rejection performance of these methods are evaluated by simulations and experiments. The integral absolute error (IAE) criterion is used to assess performance numerically. Simulation and experimental results prove the effectiveness of DDOB over the other methods.
Keywords: networked control systems; disturbance observer; Smith Predictor; time delay; DC motor speed control; COMMUNICATION DISTURBANCE OBSERVER; DESIGN; Engineering